Perlindungan Hukum Bagi Penerima Dalam Hal Pemberi Objek Jaminan Fidusia Yang Belum Didaftarkan Tanpa Persetujuan Penerima - Hariss, Abdul; Fauzia, Nur; Amanda, Gladys (Legalitas: Jurnal Hukum, 2023)
In order to improve the economy, someone sometimes needs sufficient capital to start a business, so a credit loan is needed to be able to start it. In implementing the credit agreement, creditors often also want collateral to provide security and a sense of trust. One of the credit guarantees commonly used by the public is fiduciary guarantees. The Fiduciary Guarantee has legal procedures or procedures that must be complied with so that it has binding force and can provide legal protection for the parties. The problems in this research are 1) Legal Protection for Creditors to prevent the transfer of Fiduciary objects based on Law Number 42 of 1999 concerning Fiduciary Guarantees; 2) Transfer of Fiduciary Guarantee Objects based on Law Number 42 of 1999 concerning Fiduciary Guarantees; 3) Registration of fiduciary collateral objects to avoid transfer of fiduciary collateral objects. The purpose of this research is to find out how legal protection, transfer of objects and registration of fiduciary guarantees are according to Law Number 42 of 1999 concerning Fiduciary Guarantees. This research method is normative juridical research with descriptive research characteristics, using secondary data collected through literature study. Based on the results of this research, it can be concluded that the transfer of fiduciary collateral objects that have not been registered without the creditor's consent is an action that is not justified by law (invalid). Legal protection for creditors in the event that a debtor transfers a Fiduciary Security object that has not been registered without the creditor's consent may subject the debtor to civil and criminal liability.